Competition, technological change and productivity gains: the contribution of information technologies - Stephane Ciriani; Francois Jeanjean (International Telecommunications Society (ITS), 2019)
This paper addresses the empirical relationship between the level of competition and the rate of productivity growth across thirty sectors of the French production system during the period 1978- 2015. It shows that there exists an optimal level of competition for each sector that is defined by the mark-up that maximizes the growth rate of labor productivity. The information technologies Sectors have the highest mark-ups for maximizing productivity growth. The persistence of nonoptimal mark-ups in French sectors is associated with a 0.4% loss in aggregate average annual labor productivity growth during the period (1.86%). Hence, long-term productivity growth could have reached 2.25% if mark-ups had been at their optimal level. There is a strong significant positive correlation between the optimal mark-up and the rate of Hicks-neutral technical progress in each sector. This finding implies that sectors with high technical progress, as information technologies sectors, require higher mark-ups to maximize their rate of labor productivity growth. Overall, the aggregate economy would benefit from a decrease in the gap between nonoptimal and optimal mark-ups, as such an alignment would foster productivity growth.
Keywords: O11; O31; O47; L16; 330; Technical progress; productivity growth; mark-up